Adverse events associated with ultrasonic scalers: A manufacturer and user facility device experience database analysis - Rajagopal Athmarao Thennukonda; Bhavani Rekha Natarajan (Wolters Kluwer Medknow Publications, 2015)
Background: The present study was conducted to determine the frequency and type of adverse events (AEs) associated with ultrasonic scaler reported to the Food and Drug Administration manufacturer and user facility device experience (MAUDE) database. Materials and Methods: The authors reviewed the ultrasonic scaler units (USU) related AEs reported to MAUDE from October 1, 1995, to September 31, 2015. Analyses of details collected are presented. Results: MAUDE received a total of 667 unique USU-related AE reports. Of 667 cases, MAUDE classified 628 instances (94.2%) as malfunction 27 (4%) as injurious, 10 (1.5%) as others, and 2 (0.3%) claiming the use of USU as cause of death. Of the 667 cases, 511 (76.6%) were used for endodontic application, and 147 (22%) as scaler applications. In 512 (76.8%) instances, there was separation of the tips, posing danger to patients or users, and 112 (16.8%) instances of overheating, 12 (1.8%) instances of breakage, and electrical issues in 8 (1.2%) instances. These AE resulted in 19 instances of thermal injury, 2 suspicious deaths, and hearing loss in 3 cases. In 4 cases, patient swallowed broken parts requiring additional medical care. Conclusions: Use of USU, a Class 2 device without exemption, carries a degree of risk to patient's safety, if not properly used. As of today, MAUDE data is the only reliable source of AE until another database or such study is carried out. Certain AE that has been largely anecdotal, such as hearing loss has been reported in this study. The findings from study reiterate that more in-depth analysis of AE of USU is needed. Until then operator needs to take all precautions to avoid AE when using USU.